A CONSISTENT MODEL FOR SURFACE COMPLEXATION ON BIRNESSITE (-MNO2) AND ITS APPLICATION TO A COLUMN EXPERIMENT - Appelo C.A.J.; Postma D. (My University, 1999)
Available surface complexation models for birnessite required the inclusion of bidentate bonds or the adsorption of cation-hydroxy complexes to account for experimentally observed H+/Mm+ exchange. These models contain inconsistencies and therefore the surface complexation on birnessite was re-examined. Structural data on birnessite indicate that sorption sites are located on three oxygens around a vacancy in the octahedral layer. The three oxygens together carry a charge of −2, i.e., constitute a doubly charged sorption site. Therefore a new surface complexation model was formulated using a doubly charged, diprotic, sorption site where divalent cations adsorbing via inner-sphere complexes bind to the three oxygens. Using the diprotic site concept we have remodeled the experimental data for sorption on birnessite by Murray (1975) using the surface complexation model of Dzombak and Morel (1990). Intrinsic constants for the surface complexation model were obtained with the non-linear optimization program PEST in combination with a modified version of PHREEQC (Parkhurst, 1995). The optimized model was subsequently tested against independent data sets for synthetic birnessite by Balistrieri and Murray (1982) and Wang et al. (1996). It was found to describe the experimental data well. Finally the model was tested against the results of column experiments where cations adsorbed on natural MnO2 coated sand. In this case as well, the diprotic surface complexation model gave an excellent description of the experimental results.